From an equilibrium based MOF adsorbent to a kinetic selective carbon molecular sieve for paraffin/iso-paraffin separation. Issue 96 (14th November 2016) - Li, Baiyan; Belmabkhout, Youssef; Zhang, Yiming; Bhatt, Prashant M.; He, Hongming; Zhang, Daliang; Han, Yu; Eddaoudi, Mohamed; Perman, Jason A.; Ma, Shengqian
Abstract : For the first time, a carbon molecular sieve was obtained via carbonization of a metal–organic framework, exhibiting excellent performance in paraffin/iso-paraffin separation. Abstract : We unveil a unique kinetic driven separation material for selectively removing linear paraffins from iso-paraffins via a molecular sieving mechanism. Subsequent carbonization and thermal treatment of CD-MOF-2, the cyclodextrin metal–organic framework, afforded a carbon molecular sieve with a uniform and reduced pore size of ca. 5.0 Å, and it exhibited highly selective kinetic separation of n -butane and n -pentane from iso-butane and iso-pentane, respectively.